Uma investigação sobre a eficiência entre ensino público e privado no Estado do Ceará - Joca, Bruno Pereira (2019)
The main focus of the dissertation is to investigate the main determinants in the Portuguese and mathematics proficiency tests of the 5th and 9th grade students in the state of Ceará in 2015. Therefore, the empirical exercise undertaken is to estimate the parameters to be used. from the Least Squares approach with robust standard deviation estimators to heteroscedasticity. Regarding factors associated with performance, the socioeconomic and individual factors of students stand out as the set of variables with the highest explanatory power.